2013
DOI: 10.1002/lite.201300254
|View full text |Cite
|
Sign up to set email alerts
|

Palm oil: Features and applications

Abstract: Palm fruits are the source of two distinct but related vegetable oils, namely palm oil and palm kernel oil. Palm oil has many food and industrial applications. Ever‐increasing demands for palm oil have substantially impacted its industry, creating some environmental concerns. Both types of oil are high in saturated fatty acids with potential cardiovascular risks. Several attempts have been made to reduce undesirable health and environmental impacts. However, additional research and development activities are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 3 publications
0
15
0
2
Order By: Relevance
“…Soap, hand and body lotions, fatty acid methyl esters, and epoxidized palm oil are the main industrial products that are produced from palm oil. It is also an excellent frying oil due to its non-sticky and non-foaming characteristics (NORHAIZAN et al, 2013), indicating that the lipids produced by L. starkeyi have great potential as a feedstock for biodiesel production and other oleochemical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Soap, hand and body lotions, fatty acid methyl esters, and epoxidized palm oil are the main industrial products that are produced from palm oil. It is also an excellent frying oil due to its non-sticky and non-foaming characteristics (NORHAIZAN et al, 2013), indicating that the lipids produced by L. starkeyi have great potential as a feedstock for biodiesel production and other oleochemical applications.…”
Section: Resultsmentioning
confidence: 99%
“…A research made by our group demonstrated that the mean of carotenes in the industrial CPO processed in Bahia were 526.77 μg·g −1 (Almeida et al, 2013) and this carotenoid value is extremely high when compared to other oils: sunflower (8.5±0.7 mg·L −1 ) and extra virgin olive oil (11.0±0.3 mg·L −1 ) (Andreu-Sevilla et al, 2008). On the other hand, CPO contains unusually high levels of tocotrienols (Norhaizan et al, 2013;Berger, 2005). Most other common vegetable oils have negligible contents of tocotrienols (Lin, 2011).…”
Section: Total Polar Compoundsmentioning
confidence: 93%
“…and is consumed as crude palm oil (CPO) in Africa, Southeast Asia and Brazil. Unrefined palm oil is orange-red in color and contains triglycerides with approximately 50% saturated fatty acids, 40% monounsaturated and 10% polyunsaturated fatty acids, along with carotenoids and vitamin E (Norhaizan et al, 2013;Sampaio et al, 2013). By fractionation, a liquid fraction (palm olein, rich in unsaturated compounds) and a solid fraction (palm stearin, rich in saturated compounds) can be obtained and used for different purposes in the food industry (Lin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of food crops, CPO at approximately 2 million tonnes is the leading vegetable oil in Thailand, and 1.09 million tonnes of refined palm oil (RPO) was produced in the years -2017(Office of Agricultural Economics, 2018. Palm oil is a relatively inexpensive vegetable oil, the more expensive edible oils including soybean, rapeseed, and sunflower oils (Norhaizan et al, 2013). CPO can be extracted from palm fruit by two methods, namely by wet or dry extraction (Azeman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The palm fruit are then extracted using a double screw press. The free fatty acid (FFA) content in CPO from this wet method is below 5 wt.% (Norhaizan et al, 2013). Regarding dry extraction, the palm fruit are first heated with hot air, followed by extraction in a single screw press, in small-scale palm oil plants (Mba et al, 2015).…”
Section: Introductionmentioning
confidence: 99%